Pengaruh Leverage Dan Intellectual Capital Terhadap Kinerja Perusahaan Dengan Komite Audit Sebagai Variabel Moderating Pada Perusahaan Sektor Properties & Real Estate yang Terdaftar di Bursa Efek Indonesia Periode 2017-2022 - Srie Hendraliany; Rinny Meidiyustiani; Karmia Delphina (CV. Ulil Albab Corp, 2024)
This study aims to determine the effect of leverage and changes in intangible assets on company performance, and to analyze whether the audit committee can strengthen or weaken the relationship between leverage and changes in intangible assets on company performance. The population in this study are property and real estate sector companies listed on the Indonesia Stock Exchange in the 2017-2022 financial statements. The sampling technique in this study used a purposive sampling method and obtained a sample of 43 companies. The analysis technique used is multiple linear regression analysis and Moderated Regression Analysis (MRA) using SPSS software version 22.0. The results of this study indicate that leverage and intellectual capital have a positive effect on firm performance, the effect of leverage on firm performance moderated by the audit committee variable has no effect, intellectual capital on firm performance moderated by the audit committee variable have no effect.